Case Report: New CDKN1B Mutation in Multiple Endocrine Neoplasia Type 4 and Brief Literature Review on Clinical Management - Lavezzi, Elisabetta; Brunetti, Alessandro; Smiroldo, Valeria; Nappo, Gennaro; Pedicini, Vittorio; Vitali, Eleonora; Trivellin, Giampaolo; Mazziotti, Gherardo; Lania, Andrea (Frontiers in Endocrinology, 2022)
Background The fourth type of multiple endocrine neoplasia (MEN) is known as a rare variant of MEN presenting a MEN1-like phenotype and originating from a germline mutation in CDKN1B. However, due to the small number of cases documented in the literature, the peculiar clinical features of MEN4 are still largely unknown, and clear indications about the clinical management of these patients are currently lacking. In order to widen our knowledge on MEN4 and to better typify the clinical features of this syndrome, we present two more cases of subjects with MEN4, and through a review of the current literature, we provide some possible indications on these patients’ management. Case Presentation The first report is about a man who was diagnosed with a metastatic ileal G2-NET at the age of 34. Genetic analysis revealed the mutation p.I119T (c.356T>C) of exon 1 of CDKN1B, a mutation already reported in the literature in association with early-onset pituitary adenomas. The second report is about a 76-year-old woman with a multifocal pancreatic G1-NET. Genetic analysis identified the CDKN1B mutation c.482C>G (p.S161C), described here for the first time in association with MEN4 and currently classified as a variant of uncertain significance. Both patients underwent biochemical and imaging screening for MEN1-related diseases without any pathological findings. Conclusions According to the cases reported in the literature, hyperparathyroidism is the most common clinical feature of MEN4, followed by pituitary adenoma and neuroendocrine tumors. However, MEN4 appears to be a variant of MEN with milder clinical features and later onset. Therefore, these patients might need a different and personalized approach in clinical management and a peculiar screening and follow-up strategy.